Socialization of Pokdarwis Website as Manager of the Medokan Ayu Mangrove Gardens, Surabaya: Sosialisasi Website Pokdarwis Sebagai Pengelola Kebun Raya Mangrove Medokan Ayu Surabaya - Hariadi Yutanto; Ellen Theresia Sihotang; Romi Ilham; Diah Ekaningtyas; Kartika Marta Budiana (Universitas Serang Raya, 2023)
Medokan Ayu Mangrove Botanical Garden is managed by the Medokan Ayu Tourism Awareness Group (Pokdarwis). Pokdarwis has 54 Micro, Small and Medium Enterprises (MSMEs). The management of the Pokdarwis organization and the Medokan Ayu Mangrove Gardens is still in manual way. Pokdarwis management `s views they need information systems and technology to overcome them. This condition was increasingly needed when the Medokan Ayu Pokdarwis had to temporarily close the Medokan Ayu Mangrove Botanical Gardens due to restrictions on community activities to stop the spread of Covid-19. Perbanas Hayam Wuruk University (UHW) partnership team provides a solution by presenting the Pokdarwis website with an online network. The website is socialized on how to operate, equipped with features that are integrated with MSMEs. The results of the socialization based on the evaluation provided benefits for a number of participants, so the PKM team was still providing assistance for the operation of the website. Pokdarwis Medokan Ayu also hopes that the socialization will continue in the future.